The `30-gold` ambition and Japan`s momentum for elite sport success: feasibility and policy changes - Zheng, J.; Liu, D. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
This article reviews Japan`s elite sport capabilities and analyses Japan`s recent elite sport policy changes. The policy analysis is underpinned by Kingdon`s (1984, 1995) multiple streams framework. Data were gathered from both official performance-related databases and websites, and official and semi-official documents in Japanese and English. The main findings are that (1) Japan`s `30-gold` target is not unattainable, although the narrow source of Olympic gold medals is a potential constraint; (2) the Japan Sports Agency (JSA) and the Suzuki Plan resonate with the government`s values and are largely supported by the public; and (3) policy changes were prompted/accelerated by both the political event and problem-based policy windows created by the 2011 Earthquake and other economic and social problems, Tokyo`s successful Olympic bid in 2013 and Japan`s performance at the 2016 Olympics. The study highlights the utility of the multiple streams framework and some opportunities for further advancement.